Multivocity in Topics 1.15 - Domaradzki, Mikołaj (Peitho. Examina Antiqua, 2016)
This paper discusses Aristotle’s account of multivocity (πολλαχῶς/ πλεοναχῶς λέγεται) as expounded in Topics 1.15. This article argues that an inquiry into how many ways (ποσαχῶς) something is said becomes for Aristotle a tool of dialectical examination that he employs throughout his entire philosophical career: investigating the many/multiple ways (πολλαχῶς/πλεοναχῶς) something is said allows one to recognize the ambiguity of the term in question and, consequently, to construct an adequate definition of its referent. The present study reconstructs the various strategies for detecting ambiguity and discusses its different types. Subsequently, the paper accounts for why Aristotle moves so easily from words and their meanings to things and their essences. Finally, the article presents an analysis of the connection between the many ways something is said and the various categories it is predicated in. The considerations are supported by a new translation of Topics 1.15.